Motorcyclist Is the Right-of-Way Violator: A Population-Based Study of Motorcycle Right-of-Way Crash in Taiwan - Ping-Ling Chen; Yi-Chu Chen; Chih-Wei Pai (Journal of Advanced Transportation)
The most typical and catastrophic car-motorcycle crash occurs when a car manoeuvres into the path of an approaching motorcycle at an intersection, which involves a car driver violating motorcycle’s right of way (ROW). In Taiwan, however, motorcyclists are frequently the ROW violator—they are observed to frequently infringe upon the ROW of oncoming vehicles at intersections. Such a ROW crash in which a left-turn motorcyclist crosses in front of approaching traffic appears to be a safety problem in terms of its frequency and accident consequence. Using the National Taiwan Crash Database, the present study estimates a logistic regression model to predict the likelihood of an approach-turn motorcycle-turning crash (relative to a car-turning crash). Results indicate that given a ROW crash where the rider was female, old, drunk, unlicensed, riding a moped, and on a NBU roadway, the likelihood of a motorcycle-turning crash tends to increase. Our study contributes to the existing motorcycle safety research by reporting the determinants of the unique crashes in which the motorcyclist is the ROW violator.